Multi-disciplinary approach to perioperative risk assessment and post-transplant management for liver transplantation in a patient at risk for Brugada syndrome. Issue 5 (May 2019) - Ward, Rachael A.; Ajayi, Teminioluwa; Aylward, Tanya; Byrns, Jennifer; Summers, Bryant B; Wilder, Julius
Brugada syndrome, an autosomal dominant genetic disorder, is characterised by abnormal electrocardiogram findings and increased risk of ventricular tachyarrhythmias and sudden cardiac death. Our report describes the multi-disciplinary perioperative management of a 28-year-old patient presenting to the Duke Transplant Center with a familial sodium channel gene SCN51 mutation concerning Brugada syndrome. We discuss the preparatory work-up, medication review and appropriate post-surgical follow-up for patients undergoing liver transplant surgery with cardiac monitoring.